Gait Recognition System Using Support Vector Machine and Neural Network. - Hassin AL-Asadi, Abbas Hanon; Talal AL-Abadi, Entesar Barges (Journal of Basrah Researches (Sciences), 2014)
Gait is a particular way or manner of moving on foot, whereas, gait recognition is the process of identifying an individual by the manner in which they walk. Gait is less unobtrusive biometric, which offers the possibility to identify people at a distance, without any interaction or co-operation from the subject; this is the property which makes it so attractive. This paper proposed a new method for gait recognition. In this method, firstly binary silhouette of a walking person is detected from each frame by using Eigen background method. Secondly, gait cycle is detected by using aspect ratio method; thirdly, features from each frame in gait cycle are extracted by combine two methods: model base and model free. Finally, support vector machine and neural network are used for training and testing purposes. Experimental results show that our algorithm is robust and efficient, project is designed by Matlab.